Clinical and paraclinical manifestation COVID-19 in different age children - Yu.P. Kharchenko; A.V. Zaretska; T.M. Prokopova; V.Yu. Il'ina-Stohnienko (Group of Companies Med Expert, LLC, 2022)
COVID-19 is an infectious disease caused by a new coronavirus first discovered in 2019. The infection has spread rapidly throughout the world and affects people of all ages. Thus, 12.7% of all SARS-CoV-2 patients are children. Purpose - to establish the clinical and paraclinical manifestations of the course of COVID-19 in children, depending on age to predict the severity of the disease's manifestation. Materials and methods. The 60 children aged from 3 months to 17 years old with laboratory-confirmed SARS-CoV-2 were examined. All patients underwent general clinical, laboratory, and instrumental examinations and received therapy according to Ukrainian National protocol. SARS-CoV-2 infection was confirmed by real-time PCR. Results. Thus, in young children COVID-19 begins acutely (90.0%) with intoxication (75.0%), fever (65.0%), nasal congestion (25.0%), rhinorrhea (20.0%), dry cough (60.0%), increased ESR and C-reactive protein (55.0%). The course of COVID-19 in children 4-6 years is accompanied by acute onset (85.71%), fever (85.71%), pharyngitis (85.71%), lymphopenia (28.56%), and no CT signs of lesions (71.43%). In children 7-12 years old, COVID-19 causes intoxication (88.89%), fever (83.33%), pharyngitis (55.56%), dry cough (77.78%), lymphocytosis (16.67%) with accelerated ESR (38.89%) and pneumonia (38.89%). The course of COVID-19 in children was older than 13 years old characterized by fever (73.33%), pharyngitis (66.67%), dry cough (73.33%), olfactory loss (20.0%), leukopenia (20.0%), ESR acceleration (20.0%), and a decrease in prothrombin (13.33%) without pulmonary lesions (73.33%). Conclusions. These data suggest that the severity and duration of clinical and laboratory manifestations of COVID-19 depend on the child's age. The course of COVID-19 in children of all age groups is mostly of moderate severity with a favorable prognosis ((56.67%) hospitalized children did not have any complications). Only children from 7 to 12 years old need additional attention due to the severe manifestations of intoxication (88.89%) and the risk of complications with pneumonia (38.89%). The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interests was declared by the authors.